Risk factors for sexually transmitted infections in adolescents from a secondary school - Cifuentes Zúñiga , Camila Fernanda (2021)
Objective: To determine the predominant risk factors for sexually transmitted diseases in adolescents from a secondary school in Coihueco (Chile) during the second half of 2018. Materials and methods: A cross-sectional descriptive study was conducted with a group of secondary school adolescents during the second half of 2018. A simple random sampling was performed. Data were processed using percentage calculation and entered into tables. Family bond, knowledge and risky behaviors were considered as sociodemographic variables in order to identify the predominant factors. Results: The sample consisted of people aged between 15 and 19 who were in the 3rd and 4th year of secondary education. The students demonstrated they were knowledgeable about sexually transmitted infections. Approximately 30 % had started sexual intercourse, thus showing risky behaviors such as early first sexual intercourse around 15 years of age, drug use, sex in exchange for benefits and lack of condom use as protection. There was no evidence that the students had a sexually transmitted infection. Conclusions: Considering the risk factors found in the research, it is necessary to educate the adolescents regarding the prevention of sexually transmitted infections.